2019
DOI: 10.1002/ajp.22947
|View full text |Cite
|
Sign up to set email alerts
|

Does group size matter? Captive chimpanzee (Pan troglodytes) behavior as a function of group size and composition

Abstract: The National Institutes of Health and the Association of Zoos and Aquariums recommend that captive chimpanzees be housed in multi-male, multi-female, age-diverse groups of no less than seven individuals. These recommendations are rooted in the idea that captive chimpanzee groups should be modeled after free-ranging, wild, fission-fusion chimpanzee societies. However, captive chimpanzees do not face the environmental pressures faced by wild chimpanzees, including food scarcity, inter-group competition, and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
(90 reference statements)
1
20
0
Order By: Relevance
“…In this study we measured the evenness of enclosure use, which represents the functional space of the enclosure rather than available space. We found that small variations in enclosure sizes do not associate with significant shifts in behavioural welfare of Asiatic lions, which is in line with previous studies that place more importance on enclosure design (Tan et al, 2013), complexity and species-appropriateness than enclosure area (Rose & Robert, 2013;Herrelko, Buchanan-Smith & Vick, 2015;Neal Webb, Hau & Schapiro, 2018). The correlation between enclosure size and space usage bias was weak but positive, which means that increasing enclosure sizes were associated with higher zone-usage bias.…”
Section: Discussionsupporting
confidence: 90%
“…In this study we measured the evenness of enclosure use, which represents the functional space of the enclosure rather than available space. We found that small variations in enclosure sizes do not associate with significant shifts in behavioural welfare of Asiatic lions, which is in line with previous studies that place more importance on enclosure design (Tan et al, 2013), complexity and species-appropriateness than enclosure area (Rose & Robert, 2013;Herrelko, Buchanan-Smith & Vick, 2015;Neal Webb, Hau & Schapiro, 2018). The correlation between enclosure size and space usage bias was weak but positive, which means that increasing enclosure sizes were associated with higher zone-usage bias.…”
Section: Discussionsupporting
confidence: 90%
“…Data were analyzed by using the techniques that we have published previously. [29][30][31] Briefly, durations of each behavior were averaged across all observations for each chimpanzee, with 'in-view' duration as the denominator. Average duration was then converted into a percentage of total time (that is, percentage of time of behavior = [duration of behavior / in-view duration] × 100%).…”
Section: Methodsmentioning
confidence: 99%
“…Mobility impairment scores, group size, within-group age range, and percentage of male chimpanzees in the group were used as covariates. 31 The remaining analyses focused only on elderly chimpanzees and the effects of social housing conditions on behavior and wounding. Because group size and the average age of the group were significantly negatively correlated (r = -0.78, P = 0.0001), we were unable to assess the effects of these factors independently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…that place more importance on enclosure design(Tan et al, 2013), complexity and species-appropriateness than enclosure area(Rose & Robert, 2013;Herrelko, Buchanan-Smith & Vick, 2015;Neal Webb, Hau & Schapiro, 2018). The correlation between enclosure size and space usage bias was weak but positive, which means that increasing enclosure sizes were associated with higher zone-usage bias.…”
mentioning
confidence: 99%